Myxedema with Severe Heart Failure—A Life-Threatening and Challenging Case to Treat: A Case Report and Literature Review - Yusuf Elmi; Hussam Abdelgadir; Tawfiq Almezeiny (Dr. Sulaiman Al Habib Medical Journal)
Myxedema coma is a severe life-threatening form of hypothyroidism, diagnosed by laboratory tests because of the lack of specificity in its symptoms and clinical presentation. Here, we present the case of a woman with myxedema coma who developed respiratory failure, congestive heart failure, and massive ascites, three of the uncommon manifestations of this disease. The patient was in respiratory distress upon arrival to the emergency department. Physical examination was notable for crepitation all over the chest and abdominal fluid wave, which was suggestive of ascites. The patient was managed as acute decompensated heart failure and was started on noninvasive ventilation; however, she unexpectedly started to deteriorate, and rapid sequence induction and intubation was conducted. She was then admitted to the intensive care unit. Hypothyroidism replacement therapy, aggressive diuretic regimen, and albumin replacement was initiated. The patient showed marked improvement and was weaned off sedation and extubated and was then maintained by low oxygen requirement. She was discharged from the hospital and was started on 40-mg furosemide, 25-mg spironolactone, 600-mg potassium, and 125-μg levothyroxine. On her follow-up visit, the patient showed improvement in weight that had returned to the baseline; all her symptoms were resolved. All medications were discontinued except for 100-μg levothyroxine once daily. This case report discusses an unusual presentation of myxedema coma, with heart failure and ascites concomitantly. Therefore, it is important to have a differential diagnosis for illnesses with uncertain etiology with common presentation such as acute decompensated heart failure and ascites, especially in high-risk individuals.